An Analysis of the Relationship between Job Autonomy, Feedback, and Empowering Leadership on Innovative Work Behavior: The Role of Resilience as a Mediating Factor - Yani, Yunita Risma; Hidayat, Hajan (Pusat P2M Politeknik Negeri Batam, 2025)
This research examines the relationship between job autonomy, feedback, empowering leadership, and innovative work behavior, with resilience as a mediator. Job autonomy refers to employees' freedom in performing tasks, while feedback provides performance-related information. Empowering leadership encourages employees to take initiative and make independent decisions. A quantitative approach was used, and data was collected through questionnaires from employees with over one year of experience in manufacturing and shipyard companies in Batam. Structural Equation Modeling (SEM) analyzed direct and mediating relationships. Findings indicate that job autonomy and feedback significantly enhance innovative work behavior while empowering leadership has a positive but insignificant effect. Resilience mediates these relationships, meaning employees with autonomy, constructive feedback, and empowering leaders are more innovative, especially if they have high resilience. This study offers practical insights for organizations to foster innovation by enhancing job autonomy, providing effective feedback, implementing empowering leadership, and strengthening employee resilience programs.